Sprawl and Accessibility - Robert Bruegmann (Journal of Transport and Land Use)
This essay argues that many of the assumptions that have been made about sprawl are misleading or just wrong. Nowhere has this been more the case than in debates about transportation and access. Because of this, it is not surprising that a good many of the policies advocated by proponents of Smart Growth would almost certainly lead to reduced mobility and impaired accessibility for a large part of the population. At very least, the debates over sprawl have pitted private vs. public transportation in a way that has contributed to serious underfunding of transportation infrastructure of all kinds.